Religious Literacy in Learning Fiqh based on the Sorogan Method - Dewi Anggraeni; Karnubi Karnubi (Journal EduMasa Islamic Education, 2023)
Religious literacy was very significant in shaping humanism. One of the formation processes was contextual learning of fiqh by referring to the kitab kuning (classic book). Religious literacy did not only emphasize understanding the text but also the context. This research described religious literacy through learning the fiqh of Safinatun Najah using the pesantren-style method, namely Sorogan. This qualitative research used a descriptive approach. Data collection carried out using data triangulation in the form of interviews, observation and documentation studies and analyzed referring to qualitative methods and analysis techniques referring to qualitative methods. The results of this study indicated that the process of learning religious literacy through learning fiqh was based on the Sorogan implemented through three stages: the implementation process, learning evaluation, and supporting factors. From these three stages, it was known that students’ religious literacy is more contextual by looking at various problems that exist in fiqh and were associated with everyday life. The success of implementing religious literacy in pesantren on learning fiqh was inseparable from the commitment of pesantren in producing tafaquh fi addin.